2015
DOI: 10.1088/0004-637x/800/1/25
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICALLY DISTINCT NUCLEI AND OUTFLOWING SHOCKED MOLECULAR GAS IN Arp 220

Abstract: We present the results of interferometric spectral line observations of Arp 220 at 3.5 mm and 1.2 mm from the Plateau de Bure Interferometer (PdBI), imaging the two nuclear disks in H 13 CN(1 − 0) and (3 − 2), H 13 CO + (1 − 0) and (3 − 2), and HN 13 C(3 − 2) as well as SiO(2 − 1) and (6 − 5), HC 15 N(3 − 2), and SO(6 6 − 5 5 ). The gas traced by SiO(6 − 5) has a complex and extended kinematic signature including a prominent P Cygni profile, almost identical to previous observations of HCO + (3 − 2). Spatial o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 72 publications
14
54
0
Order By: Relevance
“…This feature was previously observed with the SMA also in HCO + 3−2 (Sakamoto et al 2009) and more recently in SiO (Tunnard et al 2015). This means that a total of three absorption systems are identified at V LSR,radio ∼ 4767, 5202, and 5348 km s −1 .…”
Section: Absorption Systemssupporting
confidence: 73%
See 3 more Smart Citations
“…This feature was previously observed with the SMA also in HCO + 3−2 (Sakamoto et al 2009) and more recently in SiO (Tunnard et al 2015). This means that a total of three absorption systems are identified at V LSR,radio ∼ 4767, 5202, and 5348 km s −1 .…”
Section: Absorption Systemssupporting
confidence: 73%
“…The location of the emission of HCN and HCO + (Fig. 4a) differs from what Tunnard et al (2015) observed in SiO. This supports their idea that SiO is emitted in the gas affected by the putative outflow, but higher resolution imaging is required to conclude about this question.…”
Section: Origin and Location Of The Absorption Systemssupporting
confidence: 73%
See 2 more Smart Citations
“…When it was introduced, RADEX was recommended as a tool for interpreting molecular line ratios, primarily through diagnostic plots. However, since then, it and other LVG codes have become extensively used as general purpose tools for extracting gas conditions, especially in extragalactic targets, e.g., Krips et al (2008), Greve et al (2009), Rangwala et al (2011), Kamenetzky et al (2014), Papadopoulos et al (2014), Viti et al (2014), andTunnard et al (2015a, where the plethora of molecular lines now being observed by the state-of-the-art single-dish telescopes and interferometer arrays are allowing for modeling of multiple line ratios, and therefore more complex physical models.…”
Section: Introductionmentioning
confidence: 99%